William Tell [videorecording (Blu-Ray)] - Hamm, Nick, 1957-; Bang, Claes, 1967-; Kingsley, Ben, 1943-; Swindells, Connor, 1996-; Pryce, Jonathan (Samuel Goldwyn Films, 2025)
The narrative unfolds in the 14th Century amidst the days of the Holy Roman Empire where Europe's nations fiercely vie for supremacy and the ambitious Austrians, desiring more land, encroach upon Switzerland, a serene and pastoral nation.